Preparation of Molecularly Imprinted Cysteine Modified Zinc Sulfide Quantum Dots Based Sensor for Rapid Detection of Dopamine Hydrochloride - Xin Zhang; Meng Wang; Yating Zhang; Pan Zhao; Jiamei Cai; Yunjian Yao; Jiarong Liang (Molecules, 2023)
By combining surface molecular imprinting technology with cysteine-modified ZnS quantum dots, an elegant, molecularly imprinted cysteine-modified Mn2+: ZnS QDs (MIP@ZnS QDs) based fluorescence sensor was successfully developed. The constructed fluorescence sensor is based on a molecularly imprinted polymer (MIP) coated on the surface cysteine-modified ZnS quantum dots and used for rapid fluorescence detection of dopamine hydrochloride. The MIP@ZnS quantum dots possess the advantages of rapid response, high sensitivity, and selectivity for the detection of dopamine hydrochloride molecules. Experimental results show that the adsorption equilibrium time of MIP@ZnS QDs for dopamine hydrochloride molecules is 12 min, and it can selectively capture and bind dopamine in the sample with an imprinting factor of 29.5. The fluorescence quenching of MIP@ZnS QDs has a good linear (R2 = 0.9936) with the concentration of dopamine hydrochloride ranged from 0.01 to 1.0 μM, and the limit of detection is 3.6 nM. In addition, The MIP@ZnS QDs demonstrate good recyclability and stability and are successfully employed for detection of dopamine hydrochloride in urine samples with recoveries was 95.2% to 103.8%. The proposed MIP@ZnS QDs based fluorescent sensor provides a promising approach for food safety detection and drug analysis.